Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

every option seem to be correct, but when I wanted to evalute all the options after putting the infinity as the value for left out variable, I wasn't sure. Only Option A, says it would be 0 all the time.

lets try B

(2). x=1 and y=1

xy + z =x (y +z) 1.1 + z = 1.(1+z) 1 + z = 1 +z

what if Z is infinity, does equality hold good in that case.

Only option 5 holds true. In other cases barring case 1, only one of the values holds true. In case 1, if we put x=0 we get z=0, i.e. we get a solution but nothing to tell us that the two sides match.

If XY + Z = X(Y+Z), then which of the following must be true?

A. X=0 AND Z=0 B. X=1 AND Y=1 C. Y=1 AND Z=0 D. X=1 OR Y=0 E. X=1 OR Z=0

Please explain the answer and also why certain choices are wrong? For example what's wrong with the choice X=1 and Y=1?

\(xy+z=x(y+z)\) --> \(xy+z=xy+xz\) --> \(xy\) cancels out --> \(xz-z=0\) --> \(z(x-1)=0\) --> either \(z=0\) (in this case \(x\) can take ANY value) OR \(x=1\) (in this case \(z\) can take ANY value).

Answer: E.

To elaborate more: As the expression with \(y\) cancels out, we can say that given expression \(xy+z=x(y+z)\) does not depend on value of \(y\). Which means that \(y\) can take ANY value. So all answer choices which specify the exact value of \(y\) are wrong.

Next: "AND" in answer choices means that BOTH values must be true, but "OR" in answer choices means that EITHER value must be true.

If xy + z =x (y +z), then which of the following must be true?

(1). x=0 and z=0 (2). x=1 and y=1 (3). y=1 and z=0 (4). x=1 and y=0 (5) x=1 and z=0

Given xy+z= x (y + z) xy + z = xy + xz z = xz.

This means: 1] if x=0, then z can take any value, including 0 but not necessarily 0. Eliminate option A.

2] if z=0, then x can take any value, including 1 but not necessarily 1; moreover if we assume z not equal to 0 and divide by z on both sides. We get x=1; this means that 'z' can take non-zero values when x=1 Eliminate option E.

Now we need to examine options B, C & D.

Examining options B & D together as both suggest that x=1 when y=1 or when y=0 in the equation xy + z = xy + xz if x=1 then the eq becomes y + z = y + z. This is possible for all values of y & z not necessarily 1 or 0. Eliminate both B & D.

Examining option C: y=1 and z=0 in equation xy + z = xy + xz If y=1 then the eq becomes x + z = x + xz x + z = x(1+z) Here if z is any value other than 0 then the equation does not hold good. Hence z must be equal to 0.

I see. Where did you come up with the z*(x-1) = 0 from? Thanks. Just wanted to clarify that. It's already making a lot more sense. I should have caught this but I guess I didn't =( _________________

Hi Bunuel, As per your solution, after cancelling the xy terms, you subtracted z from xz i.e \(xz-z=0\) instead of cancelling the variable "z". Could you please explain that part. Is it because we run the risk of forgetting z=0 value? Thanks H

Bunuel wrote:

LM wrote:

Please explain the answer and also why certain choices are wrong? For example what's wrong with the choice X=1 and Y=1?

\(xy+z=x(y+z)\) --> \(xy+z=xy+xz\) --> \(xy\) cancels out --> \(xz-z=0\) --> \(z(x-1)=0\) --> either \(z=0\) (in this case \(x\) can take ANY value) OR \(x=1\) (in this case \(z\) can take ANY value).

To elaborate more: As the expression with \(y\) cancels out, we can say that given expression \(xy+z=x(y+z)\) does not depend on value of \(y\). Which means that \(y\) can take ANY value. So all answer choices which specify the exact value of \(y\) are wrong.

Next: "AND" in answer choices means that BOTH values must be true, but "OR" in answer choices means that EITHER value must be true.

Hi Bunuel, As per your solution, after cancelling the xy terms, you subtracted z from xz i.e \(xz-z=0\) instead of cancelling the variable "z". Could you please explain that part. Is it because we run the risk of forgetting z=0 value? Thanks H

i am not Bunuel but may try to explain your doubt:

when you cancel terms like that you miss some solutions for the equation; the thing is you should never ever cancel terms like that.

Hi Bunuel, As per your solution, after cancelling the xy terms, you subtracted z from xz i.e \(xz-z=0\) instead of cancelling the variable "z". Could you please explain that part. Is it because we run the risk of forgetting z=0 value? Thanks H

Bunuel wrote:

LM wrote:

Please explain the answer and also why certain choices are wrong? For example what's wrong with the choice X=1 and Y=1?

\(xy+z=x(y+z)\) --> \(xy+z=xy+xz\) --> \(xy\) cancels out --> \(xz-z=0\) --> \(z(x-1)=0\) --> either \(z=0\) (in this case \(x\) can take ANY value) OR \(x=1\) (in this case \(z\) can take ANY value).

To elaborate more: As the expression with \(y\) cancels out, we can say that given expression \(xy+z=x(y+z)\) does not depend on value of \(y\). Which means that \(y\) can take ANY value. So all answer choices which specify the exact value of \(y\) are wrong.

Next: "AND" in answer choices means that BOTH values must be true, but "OR" in answer choices means that EITHER value must be true.

Hope it helps.

We cannot reduce (divide) \(z(x-1)=0\) by \(z\) since it can be zero and division by zero is not allowed. Also if we do that we exclude the possible solution of the equation: \(z=0\). _________________

If XY + Z = X(Y+Z), then which of the following must be true?

A. X=0 AND Z=0 B. X=1 AND Y=1 C. Y=1 AND Z=0 D. X=1 OR Y=0 E. X=1 OR Z=0

Please explain the answer and also why certain choices are wrong? For example what's wrong with the choice X=1 and Y=1?

\(xy+z=x(y+z)\) --> \(xy+z=xy+xz\) --> \(xy\) cancels out --> \(xz-z=0\) --> \(z(x-1)=0\) --> either \(z=0\) (in this case \(x\) can take ANY value) OR \(x=1\) (in this case \(z\) can take ANY value).

To elaborate more: As the expression with \(y\) cancels out, we can say that given expression \(xy+z=x(y+z)\) does not depend on value of \(y\). Which means that \(y\) can take ANY value. So all answer choices which specify the exact value of \(y\) are wrong.

Next: "AND" in answer choices means that BOTH values must be true, but "OR" in answer choices means that EITHER value must be true.

Hope it helps.

I am confused because answer choice (A) also satisfies the equation. X=0 AND Z=0 as it is one of many possible solutions. If Z=0 ==> (0)Y=(0)Y. X can take an an infinity amount of values, as well as Y. Very puzzled, it seems like we have two correct answer choices in the question.

If XY + Z = X(Y+Z), then which of the following must be true?

A. X=0 AND Z=0 B. X=1 AND Y=1 C. Y=1 AND Z=0 D. X=1 OR Y=0 E. X=1 OR Z=0

Please explain the answer and also why certain choices are wrong? For example what's wrong with the choice X=1 and Y=1?

\(xy+z=x(y+z)\) --> \(xy+z=xy+xz\) --> \(xy\) cancels out --> \(xz-z=0\) --> \(z(x-1)=0\) --> either \(z=0\) (in this case \(x\) can take ANY value) OR \(x=1\) (in this case \(z\) can take ANY value).

To elaborate more: As the expression with \(y\) cancels out, we can say that given expression \(xy+z=x(y+z)\) does not depend on value of \(y\). Which means that \(y\) can take ANY value. So all answer choices which specify the exact value of \(y\) are wrong.

Next: "AND" in answer choices means that BOTH values must be true, but "OR" in answer choices means that EITHER value must be true.

Hope it helps.

I am confused because answer choice (A) also satisfies the equation. X=0 AND Z=0 as it is one of many possible solutions. If Z=0 ==> (0)Y=(0)Y. X can take an an infinity amount of values, as well as Y. Very puzzled, it seems like we have two correct answer choices in the question.

We are asked "which of the following MUST be true".

Now, if \(z=0\) then \(x\) can take ANY value. So, \(x=0\) AND \(z=0\) is not necessarily true. _________________

Part 2 of the GMAT: How I tackled the GMAT and improved a disappointing score Apologies for the month gap. I went on vacation and had to finish up a...

Cal Newport is a computer science professor at GeorgeTown University, author, blogger and is obsessed with productivity. He writes on this topic in his popular Study Hacks blog. I was...

So the last couple of weeks have seen a flurry of discussion in our MBA class Whatsapp group around Brexit, the referendum and currency exchange. Most of us believed...